Distribution of Asselian to Tastubian (early Permian) Circum-Pacific brachiopod faunas - Guang Shi; NW Archbold (1993)
Presence/absence data of Asselian to Tastubian (Early Sakmarian) brachiopod genera in the Circum-Pacific region are quantitatively assessed. A data matrix of 27 stations and 193 genera was analysed by cluster analysis and nonmetric multidimensional scaling, which revealed 5 distinctive faunal groups, each with a particular generic association. The 5 groups are interpreted as biotic provinces, namely the Arctic, Texan, Cathaysian, ?Himalayan and Indoralian. -from Authors